Complexo de pontes do Porto Camargo: progresso, redenção e impactos socioambientais 1985 - 2002 - Silva, Mateus Araújo Rafael (2021)
This dissertation aimed to problematize the impacts on nature and society in the region of Porto Camargo, a district of the municipality of Icaraíma, located in the northwest of the State of Paraná. The period analyzed was between the years 1985 to 2002 to follow the bridge construction process. In the first chapter the concept of Region was discussed, as way of thinking about the situation of Porto Camargo before the construction of the bridge. In the second chapter, the concept of progress was exposed and how it was used in a discourse to legitimize the construction. In other words, this point of view is present in photographs, reports, newspapers, whose build would develop the region. The third chapter presents the environmental impacts that bridge construction process caused in Porto Camargo through the perspective of Environmental History. For this study, Discourse Analysis and Iconography were the methods used to understand the sources of this dissertation, composed of newspapers, reports and photographs. Therefore, the bridge construction process changed the Porto Camargo region and the progress was just a discursive argument. In the development of this study, it was identified that the discourse emphasized the positive effects of the bridge construction. However, positive and negative effects were identified, mainly the consequences for nature and society.